Особливості надання медичної допомоги працюючим в нових умовах - Гречківська, Н.В.; Нагорная, А.М.; Лубянова, І.П.; Тімошина, Д.П. (Актуальні проблеми транспортної медицини, 2015)
Запропонована система медичної допомоги працюючому населенню в Україні включає структурно-функціональні підрозділи для надання (спеціалізованої) профпатологічної допомоги працюючому населенню в Україні: Центр первинної медико-санітарної допомоги (ПМСД) з мережею лікарських амбулаторій (ЛА) для забезпечення первинної медичної допомоги, кабінет профпатології консультативно-діагностичного центру (КДЦ) та Міський центр профпатології. Аналіз отриманих даних медико-соціологічного дослідження показав, що 49,3 % лікарів ЗОЗ з бюджетним фінансуванням, 40,0 % лікарів медико-санітарних частин (МСЧ) та 54,5 % лікарів приватних ЗОЗ підтримують необхідність залучення сімейного лікаря ЛА до системи надання медичної допомоги працюючим. Доцільність введення структурно-функціонального підрозділу- – кабінету профпатології з лікарем-профпатологом на базі КДЦ підтримало 72,5 % лікарів ЗОЗ з бюджетним фінансуванням, 50,0 % лікарів МСЧ та 45,5 % лікарів приватних ЗОЗ. Позитивно оцінили запропоновану систему 80,3 % лікарів ЗОЗ з бюджетним фінансуванням, 64,0 % лікарів МСЧ та 81,8 % лікарів приватних ЗОЗ. Предложенная система медицинской помощи работающему населению включает структурно-функциональные подразделения для оказания (специализированной) профпатологической медицинской помощи работающему населению в Украине: Центр первичной медико-санитарной помощи с сетью врачебных амбулаторий, кабинет профпатологии консультативно-диагностического центра (КДЦ) и Городской центр профпатологии. Анализ полученных данных медико-социологического исследования показал, что 49,3 % врачей медицинских учреждений с бюджетной формой финансирования, 40,0 % врачей медикосанитарных частей (МСЧ) и 54,5 % врачей частных медицинских учреждений поддерживают привлечение врачей семейной медицины к системе оказания медицинской помощи работающим контингентам. Введение кабинета профпатологии КДЦ позитивно оценили 72,5 % врачей бюджетных медицинских учреждений, 50,0 % — врачей МСЧ и 45,5 % врачей частных медицинских учреждений. В целом оценили положительно предложенную систему 80,3 % врачей бюджетных медицинских учреждений, 64,0 % врачей МСЧ и 81,8 % врачей частных медицинских центров. The current stage of development of Ukraine’s healthcare reform is characterized by the implementation of the family medicine. This problem is getting special emphasis with the view to European integration of Ukraine into the world community, where organization of medical care focused on the outcomes for citizens’ rights to health care through its preservation and strengthening. A system of medical care is based on investigation of material base and staff of medical organizations of different forms of ownership. The proposed system of medical care of the working population in Ukraine includes new structural and functional units to provide occupational assistance to the working population in Ukraine, which will direct the flow of workers and people with occupational diseases between structural units regardless of the source of funding or ownership. Analysis of the data of medical and sociological research showed that 49.3 % of doctors of budgetary financing, 40.0 % of doctors of sanitary units and 54.5 % of private doctors support the need to involve the family doctor to the system of medical assistance to the working population. The necessity of implementation of new structural and functional unit — the cabinet of occupational diseases physician was supported by 72.5 % of physicians of budgetary financing, 50.0 % of physicians of sanitary unit and 45.5 % of private doctors. Positively evaluated the proposed system of medical care 80.3 % of doctors budget funding, 64.0 % of physicians of sanitary unit and 81.8 % of private doctors. Conclusions. The advantage of the proposed system is the flexibility and adaptability of the health care system basing on the real conditions of existence and needs time.